2002
DOI: 10.1002/cne.10211
|View full text |Cite
|
Sign up to set email alerts
|

Projection patterns of commissural interneurons in the lumbar spinal cord of the neonatal rat

Abstract: We have studied the axonal projection patterns of commissural interneurons (CINs) in the neonatal rat spinal cord. Some CINs are integral components of the neuronal networks in the vertebrate spinal cord that generate locomotor activity. By using differential retrograde labeling protocols with fluorescent dextran amines, we show that CINs with ascending axons (ascending CINs, or aCINs) and CINs with descending axons (descending CINs, or dCINs) constitute largely different populations. We show that aCINs and dC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 81 publications
5
102
0
3
Order By: Relevance
“…Spinal motoneurons and interneuron populations were labeled retrogradely with 3 kDa of rhodamine dextran amine (Molecular Probes) in an in vitro preparation of the spinal cord, as described (23)(24)(25). The preparations were then fixed in 4% paraformaldehyde and sectioned and analyzed by immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Spinal motoneurons and interneuron populations were labeled retrogradely with 3 kDa of rhodamine dextran amine (Molecular Probes) in an in vitro preparation of the spinal cord, as described (23)(24)(25). The preparations were then fixed in 4% paraformaldehyde and sectioned and analyzed by immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Although these bilaterally projecting cells have some similarities to the inhibitory population labeled in this study, it is likely that they belong to a separate population that originates principally from laminas III-IV. It is more difficult to make satisfactory comparisons between our sample of interneurons and projections of spinal neurons with crossed axonal projections that were labeled by less localized application of tracer substances [e.g., to the whole transverse face of one side of the neonatal spinal cord in vitro (Eide et al, 1999;Stokke et al, 2002) or to the ventral and lateral part of the ventral horn (Birinyi et al, 2003)]. Nevertheless, these studies also revealed the presence of retrogradely labeled commissural neurons in the dorsal horn, which might include the inhibitory dorsal horn interneurons analyzed in this study.…”
Section: Comparison With Other Neuronal Populationsmentioning
confidence: 99%
“…In the neonatal rodent, four classes of CINs can be identified on the basis of contralateral axonal trajectory: intrasegmental (short-range CINs), intersegmental ascending, descending (aCINs, dCINs), and bifurcating [ascending, descending (adCINs)] (Eide et al, 1999;Stokke et al, 2002;Nissen et al, 2005). Since dCINs can be labeled retrogradely with calciumsensitive probes without compromising the integrity of reticulospinal projections, we have focused on this population.…”
Section: Introductionmentioning
confidence: 99%